Athletes with a Positive Psychological Response to Return to Sport Training Have Better Outcomes One and Two Years after ACL Reconstruction. Issue 7 (21st July 2017) - Zarzycki, Ryan; Failla, Mathew; Arundale, Amelia J.H.; Capin, Jacob John; Snyder-Mackler, Lynn
Objectives: Fear of re-injury and psychological readiness to return to sport have emerged as important factors affecting outcomes following anterior cruciate ligament reconstruction (ACLR). The time when athletes transition from rehabilitation to return to sport can be especially fearful. Psychological factors are potentially modifiable at this time, and improving them may lead to better outcomes. The purpose of this study was to evaluate whether athletes who showed a positive psychological response to a return to sport training program have better self-reported function and activity outcomes compared to athletes who do not have a clinically meaningful change in their psychological response. Methods: Following ACLR and completion of formal rehabilitation, 67 level I/II athletes (27 female) completed the following self-report measures at enrollment: Anterior Cruciate Ligament Return to Sport after Injury scale (ACL-RSI), International Knee Documentation Committee Subjective Knee Form (IKDC), and global rating scale (GRS). Subjects then underwent ten additional sessions, including injury prevention exercises, progressive strength training, agility training, and plyometric training, to transition the athlete to sport-specific activities. All self-report measures were repeated after training (post). Subjects subsequently completed the IKDC, a GRS, and indicated whether they had returned to the same level of sport one and two years after ACLR. Subjects were dichotomized into 2 groups based on their ACL-RSI scores. Subjects who displayed an increase in ACL-RSI score from enrollment to post that exceeded the MCID (≥1.9) were defined as having a positive psychological response (responder) to training while those who did not were defined as non-responders. Independent t-tests and chi-square tests were used to measure group differences with all outcome measures at all time points (alpha = 0.05). Results: Fourteen of sixty-seven athletes (21%) demonstrated a positive psychological response to treatment. Significant group differences were found with the IKDC one year, and two years after ACLR(Table 1). Ninety-two percent of the responder group returned to their preinjury level of sport at one year while only sixty-nine percent of the non-responder group returned (Figure 1) (Pearson chi-square=2.93, p=.087). Ninety-two percent of the responder group and eighty-eight percent of the non-responder group had returned at 2 years (Pearson chi-square=.074, p=.785). There were no group differences in time from surgery to enrollment (mean ± SD, responder: 22.6 ± 8.0 weeks, non-responder: 23.0 ±8.1 weeks, p=.882) or age (responder: 20.9 ± 6.1 years, non-responder: 22.1 ± 8.5 years, p=.624). Conclusion: Athletes who experienced a positive psychological response to return to sport training demonstrated better self-reported knee function following treatment and one and two years after ACLR. At one year, while non-responders were similar to published mean return to sport level rates (sixty-five percent in a recent meta-analysis), responders demonstrated return rates far exceeding these mean rates. The findings of this study suggest that in some athletes, return to sport training improved psychological readiness. These changes may be related to better functional and return to sport outcomes. Additional strategies may need to be added to this training program so that more athletes see improvements in their psychological response.